Contact lens materials and contact lenses

JP7642067B2Active Publication Date: 2025-03-07PEGAVISION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023525108
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-23
Filing Date
2022-02-21
Publication Date
2025-03-07
Estimated Expiration
2042-02-21

AI Technical Summary

Benefits of technology

【0024】 上述した構成により、本発明のコンタクトレンズ材料で、コストが低く、量産性及びプロセスが簡単なシリコーンハイドロゲルコンタクトレンズを製造することができる。尚、本発明に係るコンタクトレンズ材料で製造されたコンタクトレンズの表面は、優れた表面特性(例えば、親水性又は濡れ性)を有する。そのため、前記コンタクトレンズの表面に他の親水性コーティングを与える必要がない。特筆すべきことは、前記シロキサンモノマーの分子構造において、前記シロキサンの繰返し単位又はシロキシは、コンタクトレンズの酸素透過係数(DK)を向上させることができる。尚、前記主鎖及び側鎖のそれぞれにある第1の親水性セグメント及び第2の親水性セグメントによって、コンタクトレンズの表面親水性又は濡れ性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642067000001
    Figure 0007642067000001
  • Figure 0007642067000002
    Figure 0007642067000002
  • Figure 0007642067000003
    Figure 0007642067000003
Patent Text Reader

Abstract

The present invention provides a contact lens material comprising a hydrophilic monomer, a crosslinking agent, an initiator, and a siloxane monomer. [Solution] The amount of the siloxane monomer used is 5 to 50 parts by weight, where the total weight of the contact lens material is 100 parts by weight. The chemical formula of the siloxane monomer is: a H b O c N d Si e where C is a carbon atom, a is a positive number from 12 to 55, H is a hydrogen atom, b is a positive number from 29 to 121, O is an oxygen atom, c is a positive number from 4 to 17, N is a nitrogen atom, d is a positive number from 0 to 5, Si is a silicon atom, and e is a positive number from 1 to 9. The contact lens material of the present invention enables the production of silicone hydrogel contact lenses at low cost, with ease of mass production and a simple process.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to contact lens materials, and in particular to contact lens materials and contact lenses having high properties in terms of oxygen permeability, water content, and surface wettability. [Background technology]

[0002] Hydrogel contact lenses are contact lenses made from hydrogel materials, such as poly(2-hydroxyethyl methacrylate) (p-HEMA). The addition of a cross-linking agent (e.g., a compound such as ethylene glycol dimethacrylate (EGDMA)) to the poly(2-hydroxyethyl methacrylate) allows the polymer chains of the hydrogel material to interweave and bond with each other, improving their strength.

[0003] In addition, the water content of poly(2-hydroxyethyl methacrylate) is low (approximately 35 to 40%). Therefore, in order to improve the water content, one or more hydrophilic monomers (e.g., N-vinylpyrrolidone (NVP), N,N-dimethylacrylamide (DMA), methacrylic acid (MMA), etc.) are further added to the contact lens material in addition to p-HEMA. This improves the water content of the contact lens.

[0004] After adding the hydrophilic monomer, the water content of the contact lens is effectively increased (to about 70-80%). However, the higher the water content, the lower the tensile strength and toughness of the contact lens. Therefore, the water content must be properly controlled, usually 45-60%. Furthermore, the oxygen permeability (DK) of daily disposable contact lenses must be 40-70, but no matter how much the water content of hydrogel contact lenses is increased, the oxygen permeability remains at 15-35.

[0005] On the other hand, silicone hydrogel contact lenses can effectively improve the oxygen permeability (DK). Silicone hydrogel contact lenses contain hydrophilic silicon-containing polymer materials, and hydrophilic monomers (e.g., NVP, DMA, MAA, etc.) are further added and copolymerized to form silicone hydrogel contact lenses. However, since the surface of the silicone hydrogel material is hydrophobic, it is easy for bacteria to grow, which causes problems such as eye inflammation. Therefore, the surface of the silicone hydrogel material usually needs to be modified to improve the wettability of the material surface.

[0006] Therefore, there is a need for a new silicone hydrogel material to solve the above problems. Summary of the Invention [Problem to be solved by the invention]

[0007] The technical problem that the present invention seeks to solve is to provide a contact lens material and a contact lens that address the shortcomings of the prior art. [Means for solving the problem]

[0008] In order to solve the above technical problems, one technical means adopted by the present invention provides a contact lens material comprising a hydrophilic monomer, a crosslinking agent, an initiator, and a siloxane monomer. The amount of the siloxane monomer used is 5 to 50 parts by weight, where the total weight of the contact lens material is 100 parts by weight. The chemical formula of the siloxane monomer is the following formula: (II-1) or Formula (II-2) As shown in the figure.

[0009] [ka] [ka]

[0010] In formula (II-1) and formula (II-2), R 1 is H or a methyl group (-CH 3 ) and X 1 is O or NR 8 and X 2 is CH-OR 9 Or it may be absent, R 2 is a methyl group (-CH 3 ) and R 3 、R 4 、R 7 、R 8 and R 9 are independently H, a methyl group (-CH 3 ), or JPEG0007642067000003.jpg1642 and R 10 is H or a methyl group (-CH 3 ) and R 5 and R 6 each independently represents an alkyl group, an aryl group, an alkoxy group, an aryloxy group, or an OSiR 11 R 12 R 13 and R 11 、R 12 , and R 13 each independently represents an alkyl group, an aryl group, an alkoxy group, or an aryloxy group having 1 to 10 carbon atoms, a is an integer of 1 to 3; c and n are independently positive numbers of 0 to 3; b is a positive number of 0 to 8.

[0011] Preferably, the molecular weight of the siloxane monomer is 400 to 1,200.

[0012] Preferably, the main chain of the molecular structure of the siloxane monomer has siloxane repeat units or siloxy, and the main chain has a first hydrophilic segment composed of a structural fragment of 1-aminoglycerol modified with a substituent shown in formula (I-1), and the side chain of the molecular structure of the siloxane monomer further has a second hydrophilic segment composed of polyethylene glycol (PEG).

[0013] [ka]

[0014] Preferably, the molecular structure of the siloxane monomer has a hydrophilic side chain grafted to the main chain, the hydrophilic side chain having x carbon atoms and y oxygen atoms, where 0≦x+y≦10, and at least one hydrophilic functional group at an end of the hydrophilic side chain remote from the main chain, the hydrophilic functional group being a hydroxyl functional group (-OH group) or an alkoxy functional group.

[0020] Preferably, the hydrophilic monomer is selected from at least one of the group consisting of N-vinylpyrrolidone (NVP), 2-hydroxyethyl methacrylate (HEMA), N-(2-hydroxyethyl)acrylamide (HEAA), glycidyl methacrylate (GMA), glycerol monomethacrylate (GMMA), methacrylic acid (MMA), acrylic acid (AA), N,N-dimethylacrylamide (DMA), N,N-dimethylmethacrylamide, N-vinyl-N-methylacetamide, glycine vinyl carbonate, 2-methacryloyloxyethyl phosphorylcholine, and 2-hydroxybutyl methacrylate. Preferably, the amount of the hydrophilic monomer used is 40 to 90 parts by weight, based on 100 parts by weight of the total weight of the contact lens material.

[0021] Preferably, the crosslinker is selected from at least one of the group consisting of ethylene glycol dimethacrylate (EGDMA), diethylene glycol dimethacrylate (DEGDMA), triethylene glycol dimethacrylate (TEGDMA), tetraethylene glycol dimethacrylate (TTEGDMA), allyl methacrylate (AMA), ethylene glycol diallyl ether (EGDAE), triethylene glycol diallyl ether (TEGDAE), tetraethylene glycol diallyl ether (TTEGDAE), 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,1-trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, tetraethylene glycol diacrylate, ethylene diacrylamide, 1,4-di(acrylamido)butene, and polyethylene glycol diacrylate. Preferably, the amount of the crosslinking agent used is 0.1 to 5 parts by weight, based on 100 parts by weight of the total weight of the contact lens material.

[0022] Preferably, the initiator is selected from the group consisting of di-H5-cyclopentadienylbis[2,6-difluoro-3-(pyrrol-1-yl)phenyl]titanium(4), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,2'-azodi(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2,4-dimethyl)valeronitrile, 2,2'-azobis(2-methyl)propionitrile, 2,2'-azobis(2-methyl)butyronitrile, and benzoyl peroxide. When Preferably, the amount of the initiator used is 0.01 to 2 parts by weight, based on 100 parts by weight of the total weight of the contact lens material.

[0023] In order to solve the above technical problems, another technical solution adopted in the present invention provides a contact lens made of the contact lens material, which has a water content of 45wt% to 80wt%, an oxygen permeability coefficient of 40 barrers or more, an elastic modulus of 1.5MPa or less, and Dynamic contact below 80° Corner Yes. Effect of the Invention

[0024] According to the above-mentioned configuration, the contact lens material of the present invention can be used to manufacture silicone hydrogel contact lenses at low cost, with ease of mass production and processing. The surface of the contact lens manufactured using the contact lens material of the present invention has excellent surface properties (e.g., hydrophilicity or wettability). Therefore, it is not necessary to provide another hydrophilic coating on the surface of the contact lens. It is noteworthy that in the molecular structure of the siloxane monomer, the siloxane repeating unit or siloxy can improve the oxygen permeability (DK) of the contact lens. The first hydrophilic segment and the second hydrophilic segment in the main chain and the side chain, respectively, can improve the surface hydrophilicity or wettability of the contact lens. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In order to better understand the features and technical contents of the present invention, please refer to the following detailed description of the present invention. However, the detailed description provided is only for reference and explanation, and is not intended to limit the scope of the present invention.

[0026] Hereinafter, the embodiments of the present invention will be described in accordance with certain specific embodiments, and those skilled in the art can understand the advantages and effects of the present invention based on the contents disclosed in this specification. The present invention can be implemented or applied in other different specific embodiments, and various modifications and changes can be made to each detail in this specification based on different perspectives and applications without departing from the concept of the present invention. The technical contents of the present invention will be described in more detail based on the following embodiments, but the disclosed contents do not limit the protection scope of the present invention.

[0027] It should be understood that although the present specification may use terms such as "first" and "second" to describe various constituents or characteristic compounds, these constituents or characteristic compounds are not limited by these terms. These terms are primarily intended to distinguish one constituent from another, or one characteristic compound from another. In addition, the term "or" used herein may include any one or more combinations of the associated listed items, depending on the actual situation.

[0028] In this specification, when a specific numerical range is described, the notation "a certain value to a certain value" is adopted. The meaning includes any numerical value included in the numerical range and a narrower numerical range limited by any numerical range included in the numerical range. Specifically, it is as shown in the arbitrary numerical value and the narrower numerical range clearly described in the specification. In addition, in order to simplify the description of the specification, the structure of each compound or group in this specification may be represented by a skeletal formula so as to omit the carbon atoms, hydrogen atoms, and carbon-hydrogen bonds contained in the structure. However, when a specific atom or group is depicted in the structural formula, the atom or group in the structural formula is adopted.

[0029] [Contact lens materials] An embodiment of the present invention provides a material for contact lenses that has a hydrophilic surface and is capable of forming contact lenses having high oxygen permeability and high water content. A contact lens material according to an embodiment of the present invention includes a siloxane monomer, a hydrophilic monomer, a crosslinking agent, and an initiator.

[0030] The amount of the siloxane monomer used is preferably 5 to 50 parts by weight, and particularly preferably 20 to 40 parts by weight, relative to 100 parts by weight of the total weight of the contact lens material, although the present invention is not limited thereto.

[0031] The chemical formula of the siloxane monomer is as shown in formula (I) below.

[0032] C a H b O c N d S e Formula (I)

[0033] In the formula, C is a carbon atom, and a is the number of carbon atoms present in the siloxane monomer. a is preferably a positive number from 12 to 55, and more preferably from 17 to 32. H is a hydrogen atom, and b is the number of hydrogen atoms present in the siloxane monomer. b is preferably a positive number from 29 to 121, and more preferably from 38 to 71. O is an oxygen atom, and c is the number of oxygen atoms present in the siloxane monomer. c is preferably a positive number from 4 to 17, and more preferably from 6 to 14. N is a nitrogen atom, and d is the number of nitrogen atoms present in the siloxane monomer. d is preferably a positive number from 0 to 5, and more preferably from 0 to 3. Si is a silicon atom, and e is the number of silicon atoms present in the siloxane monomer. e is preferably a positive number from 1 to 9, and more preferably from 3 to 5.

[0034] In one embodiment of the present invention, the molecular weight of the siloxane monomer is preferably 400 to 1,200, and more preferably 500 to 700.

[0035] In one embodiment of the present invention, the main chain of the molecular structure of the siloxane monomer has siloxane repeat units or siloxy, and the main chain has a first hydrophilic segment composed of a structural fragment of 1-aminoglycerol modified with a substituent represented by formula (I-1), and the side chain of the molecular structure of the siloxane monomer has a second hydrophilic segment composed of polyethylene glycol (PEG).

[0036] [ka]

[0037] In one embodiment of the present invention, the molecular structure of the siloxane monomer further comprises a hydrophilic side chain grafted to the main chain, wherein the hydrophilic side chain has x carbon atoms and y oxygen atoms, where 0≦x+y≦10, and the hydrophilic side chain has at least one hydrophilic functional group at its end remote from the main chain, such as a hydroxyl functional group (-OH group) or an alkoxy functional group.

[0038] According to the above-mentioned configuration, the contact lens material of the present invention can be used to manufacture a silicone hydrogel contact lens at low cost, with mass production and simple process. The surface of the contact lens manufactured with the contact lens material of the present invention has excellent surface properties (e.g., hydrophilicity or wettability). Therefore, it is not necessary to provide another hydrophilic coating on the surface of the contact lens. It is noteworthy that in the molecular structure of the siloxane monomer, the siloxane repeat unit or siloxy can improve the oxygen permeability (DK) of the contact lens. The first hydrophilic segment and the second hydrophilic segment in the main chain and the side chain, respectively, can improve the surface hydrophilicity or wettability of the contact lens.

[0039] In one embodiment of the present invention, the chemical formula of the siloxane monomer is as shown in the following formula (I-1), formula (I-2), and formula (I-3).

[0040] C 24 H 53 O9NSi3 formula (I-1)

[0041] C 28 H 61 O 11 NSi3 formula (I-2)

[0042] C 17 H 38 O6Si3 formula (I-3)

[0043] Wherein, the molecular weight of the siloxane monomer shown in the formula (I-1) is 583.9354, the molecular weight of the siloxane monomer shown in the formula (I-2) is 672.0405, and the molecular weight of the siloxane monomer shown in the formula (I-3) is 422.7365.

[0044] In one embodiment of the present invention, the skeletal formula of the siloxane monomer represented by formula (I) is formula (II-1) or formula (II-2).

[0045] [ka]

[0046] [ka]

[0047] Among them, R 1 is H or a methyl group (-CH3), and X 1 is O or NR 8 and X 2 is CH-OR 9 or may be absent, R 2 is a methyl group (-CH3) or may be absent, R 3 , R 4 , R 7 , R 8 and R 9 are each independently (i.e., the substituents may be the same or different) H or a methyl group (-CH3), or JPEG0007642067000008.jpg1138, R 10 is H or a methyl group (-CH3), and R 5 and R 6 each independently represents an alkyl group, an aryl group, an alkoxy group, an aryloxy group, or an OSiR group having 1 to 10 carbon atoms (i.e., the substituents may be the same or different). 11 R 12 R 13and R 11 , R 12 and R 13 are independently (i.e., the substituents may be the same or different) an alkyl group, an aryl group, an alkoxy group, or an aryloxy group having 1 to 10 carbon atoms, in which a, c, and n are each independently (the numbers may be the same or different) a positive number of 0 to 3 (preferably 1 to 3), and b is a positive number of 0 to 8 (preferably 1 to 8).

[0048] In the structural formula (II-1) or (II-2), JPEG0007642067000009.jpg2438 is siloxane repeat units or siloxy.

[0049] To explain further, R 3 or R 7 Substituents of JPEG0007642067000010.jpg1138 is the second hydrophilic segment made of polyethylene glycol (PEG).

[0050] To explain further, X 1 and X 2 is a backbone atom or group of the main chain, or a hydrophilic branch.

[0051] More specifically, at least one hydroxyl group is a substituent on the backbone and at least one oxygen, nitrogen or both are backbone atoms, and the siloxane monomer is an ionic monomer, a linear monomer or a branched monomer.

[0052] In a first specific embodiment of the present invention, the substituents corresponding to the formula (II-1) in the siloxane monomer shown in the formula (I-1) are as follows: R 1 =CH3;X 1=O;X 2 =CH-OR 9 ;a=c=1;b=0;R 2 =none;R 3 = JPEG0007642067000011.jpg1137,n=2;R 4 =R 7 =R 9 =R 10 =H;R 5 =R 6 =OSiR 11 R 12 R 13 ,R 11 =R 12 =R 13 =CH3.

[0053] In a second specific embodiment of the present invention, the substituents corresponding to the formula (II-1) in the siloxane monomer shown in the formula (I-2) are as follows: R 1 =R 5 =R 6 =CH3;X 1 =O;X 2 =CH-OR 9 ;a=c=1;b=2;R 2 =none;R 3 =R 7 = JPEG0007642067000012.jpg1037,n=2;R 4 =R 9 =R 10 =H.

[0054] In a third specific embodiment of the present invention, the substituents corresponding to the formula (II-1) in the siloxane monomer shown in the formula (I-3) are as follows: R 1 =CH3;X 1 =O;X 2 =CH-OR 9 ;a=b=0;c=1;R 5 =R 6 =OSiR 11 R 12 R 13 ,R 11 =R 12 =R 13 =CH3;R7 =R 9 =H.

[0055] In one embodiment of the present invention, the hydrophilic monomer is selected from the group consisting of N-vinyl pyrrolidone (NVP), 2-hydroxyethyl methacrylate (HEMA), N-(2-hydroxyethyl)acrylamide (HEAA), glyceryl methacrylate (GMA), glycerol mono-methacrylate (GMMA), methacrylic acid (MAA), acrylic acid (AA), N,N-dimethylmethacrylamide (DMA), N-vinyl-N-methyl acetamide, glycine vinyl carbonate, 2-methacryloyloxyethyl phosphorylcholine, and 2-hydroxy-butyl methacrylate. The copolymer is selected from at least one of the group consisting of:

[0056] More specifically, the amount of the hydrophilic monomer used is preferably 40 to 90 parts by weight, and particularly preferably 45 to 85 parts by weight, relative to 100 parts by weight of the total weight of the contact lens composition, although the present invention is not limited thereto.

[0057] In one embodiment of the invention, the crosslinking agent is selected from the group consisting of ethylene glycol di(methacrylate), EGDMA, di(ethylene glycol) di(methacrylate), DEGDMA, tri(ethylene glycol) di(methacrylate), TEGDMA, tetra(ethylene glycol) di(methacrylate), TTEGDMA, allyl methacrylate (AMA), ethylene glycol di(allyl ether), EGDAE, tri(ethylene glycol) di(allyl ether), TEGDAE, tetra(ethylene glycol) di(allyl ether), AMA, ...AMA, ethylene glycol di(allyl ether), EGDAE, tri(ethylene glycol) di(allyl ether), TEGDAE, tetra(ethylene glycol) di(allyl ether), AMA, ethylene glycol di(allyl ether), AMA, ethylene glycol di(allyl ether), AMA, ethylene glycol di(allyl ether), AMA, ethylene glycol di(allyl ether), AMA, ethylene glycol di(allyl ether), AMA, ethylene glycol di(allyl ether), AMA, ether, TTEGDAE), 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,1-tri(methylolpropane) tri(methacrylate), trimethylolpropane tri(acrylate), pentaerythritol tetra(acrylate), tetra(ethylene glycol) di(acrylate), ethylene di(acrylamide), butylene 1,4-di(acrylamide), and polyethylene glycol diacrylate. The polymer is selected from at least one of the group consisting of:

[0058] More specifically, the amount of the crosslinking agent used is preferably 0.1 to 5 parts by weight, and particularly preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of the total weight of the contact lens composition, although the present invention is not limited thereto.

[0059] In one embodiment of the invention, the initiator is a photoinitiator.

[0060] In one embodiment of the invention, the initiator is selected from at least one of the group consisting of di-H5-cyclopentadienylbis[2,6-difluoro-3-(pyrrol-1-yl)-phenyl]titanium(4), phenylbis-(2,4,6-trimethylbenzoyl)-phosphine oxide, and 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0061] In one embodiment of the present invention, the initiator may be selected from at least one of the group consisting of 2,2'-azodi(2,4-dimethylvaleronitrile), ADVN, 2,2'-azobis(2-methylpropionitrile), AIBN, 2,2'-azobis(2,4-dimethyl)valeronitrile, 2,2'-azobis(2-methyl)propionitrile, 2,2'-azobis(2-methyl)butyronitrile, and benzoyl peroxide, but the present invention is not limited thereto.

[0062] More specifically, the amount of the initiator used is preferably 0.01 to 2 parts by weight, and particularly preferably 0.05 to 1 part by weight, relative to 100 parts by weight of the total weight of the contact lens composition, although the present invention is not limited thereto.

[0063] In order to improve the ultraviolet blocking ability of the contact lens material, in one embodiment of the present invention, the contact lens material further comprises an ultraviolet blocking monomer. The amount of the ultraviolet blocking monomer used is 0.30 parts by weight to 1.80 parts by weight based on 100 parts by weight of the total weight of the contact lens material. The ultraviolet blocking monomer is at least one selected from the group consisting of a monomer having benzophenone and a benzotriazole.

[0064] In one embodiment of the present invention, in order to improve the solubility of the contact lens material, the contact lens material further comprises a co-solvent. The amount of the co-solvent used is 3 to 15 parts by weight, based on 100 parts by weight of the total weight of the contact lens composition. The co-solvent is selected from at least one of the group consisting of glycerol (GLY), 2-propanol (isopropyl alcohol), n-butanol, tert-butanol, tert-amyl alcohol, and n-hexanol.

[0065] In order to impart a particular color to the contact lens material, in some embodiments of the present invention, the contact lens material further comprises a dye, the amount of the dye being 0.002 parts by weight to 0.050 parts by weight based on 100 parts by weight of the total weight of the contact lens material. The dye is selected from at least one of the group consisting of Reactive Blue 19 (disodium, 1-amino-9,10-dioxo-4-[3-(2-sulfonatooxyethylsulfonyl)anilino]anthracene-2-sulfonate), Sudan III (1-[4-(Phenylazo)phenylazo]-2-naphthol, Sudan III), Indigo (2,2'-Bis(2,3-dihydro-3-oxoindolylidene), Indigo), and Quinophthalone (disodium 2-(1,3-dioxo-2,3-dihydro-1H-inden-2-yl)quinolone-6,8-disul fonate, Quinoline yellow).

[0066] [Contact lens manufacturing method] In an embodiment of the present invention, a method for manufacturing a contact lens is further provided. The method for manufacturing a contact lens includes injecting the contact lens material into a mold for manufacturing a contact lens and subjecting the contact lens material to a hardening molding process to form a semi-finished dry contact lens. Next, the semi-finished dry contact lens is left in a buffer solution so that the semi-finished dry contact lens swells (hydration process). Then, the buffer solution is filled into a packaging container, and the contact lens is immersed in the buffer solution. Next, a sealing process and a sterilization process are performed, and then the manufacturing of the contact lens is completed.

[0067] [Contact lenses] In an embodiment of the present invention, there is further provided a contact lens, which is made of the contact lens material according to the above embodiment. According to the formulation of the contact lens according to the above embodiment, the contact lens according to the embodiment of the present invention has high properties in terms of oxygen permeability, water content, and surface wettability.

[0068] A contact lens made of the contact lens material of the present invention has superior physicochemical properties. More specifically, the contact lens has (a) a water content of 45wt% to 80wt% (preferably 65wt% to 80wt%), (b) an oxygen permeability of 40 barrers or more (preferably 40barrers to 60barrers), (c) an elastic modulus of 1.5MPa or less (preferably 0.3MPa to 0.6MPa), (d) a dynamic contact angle of 80° or less (preferably 60° or less, more preferably 30° or less), (e) a refractive index of 1.350 to 1.442, and (f) a lubricity of 5 to 10 (preferably 6 to 9).

[0069] [Experimental data and measurement results] The present invention will be described in detail below with reference to Examples S1 to S11. However, these Examples are provided for the purpose of understanding the present invention, and the present invention is not limited thereto.

[0070] The manufacturing method of Examples S1 to S11 includes forming a semi-finished dry contact lens by injecting the contact lens material into a mold for manufacturing a contact lens and subjecting the contact lens material to a hardening molding process. Next, the semi-finished dry contact lens is left in a buffer solution so that the semi-finished dry contact lens swells (hydration process). Then, the buffer solution is filled into a packaging container, and the contact lens is immersed in the buffer solution. Next, a sealing process (sealing temperature is about 125°C) and a sterilization process (sterilization time is about 30 minutes) are performed, and then the manufacturing of the contact lens is completed.

[0071] Wherein, the contact lens material mainly includes a siloxane monomer, a hydrophilic monomer, a crosslinking agent, and an initiator. The manufacturing methods of Examples S1 to S11 are almost the same, and the difference between them is that the amount of each component of the contact lens material according to Examples S1 to S11 is different, and the siloxane monomer used is also different. Wherein, Examples S1 to S3 adopted a siloxane monomer having the above chemical formula (I-1) and corresponding to the first specific embodiment. Examples S4 to S6 adopted a siloxane monomer having the above chemical formula (I-2) and corresponding to the second specific embodiment. Examples S7 and S8 adopted a siloxane monomer having the above chemical formula (I-1) and corresponding to the first specific embodiment, and a siloxane monomer having the above chemical formula (I-2) and corresponding to the second specific embodiment. Example S9 adopted a siloxane monomer having the above chemical formula (I-1) and corresponding to the first specific embodiment, and a siloxane monomer having the above chemical formula (I-3) and corresponding to the third specific embodiment. Example S10 adopted a siloxane monomer having the above chemical formula (I-2) and corresponding to the second specific embodiment, and a siloxane monomer having the above chemical formula (I-3) and corresponding to the third specific embodiment. Example S11 adopted a siloxane monomer having the above chemical formula (I-3) and corresponding to the third specific embodiment. The formulations of Examples S1 to S11 are as shown in Table 1 below.

[0072] The chemical structures of the siloxane monomers used in Examples S1 to S11 all contain carbon (C), hydrogen (H), oxygen (O) and silicon (Si) atoms, but differ in the amount of nitrogen (N) atoms. The siloxane monomer having the above chemical formula (I-3) and corresponding to the third specific embodiment does not contain a nitrogen atom, so that the contact lens materials according to the embodiment of the present invention can be used as a control group having contact lens materials with different compositions of nitrogen, oxygen and silicon.

[0073] The siloxane monomers employed in Examples S1 to S11 all provide good results in the following physicochemical properties of the contact lens. The physicochemical properties include the water content (wt%) of the contact lens body, the oxygen permeability (DK) of the contact lens body, the elastic modulus (MPa) of the contact lens body, the dynamic contact angle of the contact lens surface, and the lubricity of the contact lens surface. The measurement method of the physicochemical properties of the contact lens is described as follows, and the measurement results are shown in Table 5 below.

[0074] Regarding the water content (wt%) of the contact lens body, the equilibrium water content was measured by transferring water to the contact lens surface, then weighing the lens to obtain the weight of the hydrated lens. The lens was dried in an oven and measured in a dry state to obtain the weight of the dry lens. The weight difference was obtained by subtracting the weight of the dry lens from the weight of the hydrated lens. Equilibrium water content (wt%) = (weight difference / weight of hydrated lens) x 100%.

[0075] Regarding the oxygen permeability (DK) of the contact lens body, the oxygen permeability was measured using an O2 permeometer based on the polarographic method described in ISO 9913-1. The measurement was performed by immersing the sample in pure water equilibrated for at least 12 hours. The oxygen permeability was then measured in a phosphate buffer solution at 35°C using an O2 permeometer (Model 201T manufactured by Rheder Development Company). The unit of oxygen permeability is Barrer.

[0076] The elastic modulus (MPa) of the contact lens body was measured using a tensile tester (Zwick Z0.5). Lens samples were cut to a width of 2 mm. Before the measurement, the thickness of the sample was measured using a micrometer. When the measurement started, the moving speed for stretching the sample, the length of the sample, and the distance between the chucks were kept constant. During the measurement, the samples were left in buffered saline. The unit of elastic modulus was MPa, and the unit of elongation was %.

[0077] The dynamic contact angle (°) of the contact lens surface was measured by the captive bubble method. In this method, the silicone hydrogel contact lens was appropriately sandwiched between two hard plastics to make the center of the lens relatively flat, and then the lens was immersed in a small can containing a solution of borate buffered saline. Then, bubbles were appropriately introduced to the lens surface and allowed to settle on the surface. After that, a photograph was taken with a digital camera, and the left and right contact angles were obtained from the plot using a calculator program, and the average of the left and right contact angles was recorded.

[0078] The lubricity of the contact lens surface was blindly assessed by 10 people on a scale of 1 to 10. The higher the score, the better the lubricity of the contact lens surface.

[0079] Table 1 shows the formulations of the contact lens materials of Examples S1 to S11, in which the total weight of the contact lens materials was 100 parts by weight.

[0080] [Table 1]

[0081] [Table 2]

[0082] [Experimental results] Table 2 shows the properties of the contact lens surfaces of Examples S1 to S11, such as dynamic contact angle and lubricity. The lower the dynamic contact angle, the more hydrophilic the contact lens surface is. Many highly hydrophilic surfaces have a contact angle of 0° to 30°. The lubricity of the contact lens surfaces was blindly evaluated by 10 people (1 to 10). The higher the fraction, the more lubricious the contact lens surface is. The measurement results of the dynamic contact angle and lubricity are shown in Table 2.

[0083] The following physicochemical properties of the contact lens were good when any of the siloxane monomers used in Examples S1 to S11 were used. Among them, the hydrophilicity or wettability of the contact lens surface in Examples S1 to S8 showed better results. To explain further, in the chemical structure of the siloxane monomer in Examples S1 to S8, the oxygen atom can improve the surface hydrophilicity of the contact lens material through hydrogen bonds and water molecule bonds. The nitrogen atom, in an ionic state, easily bonds to water molecules through hydrogen bonds.

[0084] Generally, the higher the silicon atom content, the more hydrophobic the contact lens surface becomes, but the chemical structures of the siloxane monomers according to Examples S1 to S8 contain relatively many oxygen and nitrogen atoms, so that the contact lens surface can maintain good hydrophilicity and lubricity, making it unnecessary to provide a hydrophilic coating on the surface of the contact lenses manufactured with the formulations of Examples S1 to S8.

[0085] [Advantageous Effects of the Embodiments] The advantageous effect of the present invention is that the contact lens material according to the embodiment of the present invention can produce silicone hydrogel contact lenses with low cost, mass production and simple process. The surface of the contact lens produced by the contact lens material according to the present invention has excellent surface properties (e.g., hydrophilicity or wettability). Therefore, there is no need to provide another hydrophilic coating on the surface of the contact lens. It is noteworthy that in the molecular structure of the siloxane monomer, the siloxane repeat unit or siloxy can improve the oxygen permeability (DK) of the contact lens. The first hydrophilic segment and the second hydrophilic segment in the main chain and the side chain, respectively, can improve the surface hydrophilicity or wettability of the contact lens.

[0086] The above disclosure is merely a preferred embodiment of the present invention, and the scope of the claims of the present invention is not limited thereto. Therefore, all equivalent technical modifications made by utilizing the specification and drawings of the present invention are included in the scope of the claims of the present invention.

Claims

1. 1. A contact lens material comprising a hydrophilic monomer, a crosslinker, an initiator, and a siloxane monomer, the amount of the siloxane monomer used is 5 parts by weight to 50 parts by weight, based on 100 parts by weight of the total weight of the contact lens material; The chemical formula of the siloxane monomer is as shown in formula (II-1) or formula (II-2): Contact lens materials. 【Chemistry 2】 【Chemistry 3】 In formula (II-1) and formula (II-2), R 1 is H or a methyl group (-CH 3 ) and X 1 is O or NR 8 and X 2 is CH-OR 9 Or it may be absent, R 2 is a methyl group (-CH 3 ) and R 3 , R 4 , R 7 , R 8 and R 9 are independently H, a methyl group (-CH 3 ), or 【change】 and R 10 is H or a methyl group (-CH 3 ) and R 5 and R 6 each independently represents an alkyl group, an aryl group, an alkoxy group, an aryloxy group, or an OSiR 11 R 12 R 13 and R 11 , R 12 , and R 13 each independently represents an alkyl group, an aryl group, an alkoxy group, or an aryloxy group having 1 to 10 carbon atoms, a is an integer of 1 to 3; c and n are independently positive numbers of 0 to 3; b is a positive number of 0 to 8.

2. The molecular weight of the siloxane monomer is 400 to 1,200; The contact lens material of claim 1.

3. The main chain of the molecular structure of the siloxane monomer has siloxane repeat units or siloxy, and the main chain further has a first hydrophilic segment composed of a structural fragment of 1-aminoglycerol modified with a substituent represented by formula (I-1), The side chain of the molecular structure of the siloxane monomer further has a second hydrophilic segment composed of polyethylene glycol (PEG). The contact lens material of claim 1. 【Chemistry 1】

4. The molecular structure of the siloxane monomer has a hydrophilic side chain grafted to the main chain, the hydrophilic side chain has x carbon atoms and y oxygen atoms, where 0≦x+y≦10; The hydrophilic side chain has a hydrophilic functional group at an end remote from the main chain, the hydrophilic functional group being a hydroxyl functional group (-OH group) or an alkoxy functional group. The contact lens material according to claim 3.

5. the hydrophilic monomer is selected from at least one of the group consisting of N-vinylpyrrolidone (NVP), 2-hydroxyethyl methacrylate (HEMA), N-(2-hydroxyethyl)acrylamide (HEAA), glycidyl methacrylate (GMA), glycerol monomethacrylate (GMMA), methacrylic acid (MMA), acrylic acid (AA), N,N-dimethylacrylamide (DMA), N,N-dimethylmethacrylamide, N-vinyl-N-methylacetamide, glycine vinyl carbonate, 2-methacryloyloxyethyl phosphorylcholine, and 2-hydroxybutyl methacrylate; The amount of the hydrophilic monomer used is 40 parts by weight to 90 parts by weight, based on 100 parts by weight of the total weight of the contact lens material. The contact lens material of claim 1.

6. the crosslinking agent is selected from at least one of the group consisting of ethylene glycol dimethacrylate (EGDMA), diethylene glycol dimethacrylate (DEGDMA), triethylene glycol dimethacrylate (TEGDMA), tetraethylene glycol dimethacrylate (TTEGDMA), allyl methacrylate (AMA), ethylene glycol diallyl ether (EGDAE), triethylene glycol diallyl ether (TEGDAE), tetraethylene glycol diallyl ether (TTEGDAE), 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,1-trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, tetraethylene glycol diacrylate, ethylene diacrylamide, 1,4-di(acrylamido)butene, and polyethylene glycol diacrylate; The amount of the crosslinking agent used is 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the total weight of the contact lens material. The contact lens material of claim 1.

7. the initiator is selected from at least one of the group consisting of di-H5-cyclopentadienylbis[2,6-difluoro-3-(pyrrol-1-yl)phenyl]titanium(4), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,2'-azodi(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2,4-dimethyl)valeronitrile, 2,2'-azobis(2-methyl)propionitrile, 2,2'-azobis(2-methyl)butyronitrile, and benzoyl peroxide; The amount of the initiator used is 0.01 to 2 parts by weight based on 100 parts by weight of the total weight of the contact lens material. The contact lens material of claim 1.

8. A contact lens made of the contact lens material according to any one of claims 1 to 7, The contact lens is characterized in that it has a water content of 45 wt% to 80 wt%, an oxygen permeability coefficient of 40 barrers or more, an elastic modulus of 1.5 MPa or less, and a dynamic contact angle of 80° or less. Contact lenses.

Citation Information

Patent Citations

  • Primary Amine-Containing Silicone Hydrogel Contact Lenses and Related Compositions and Methods

    JP2016524178A

  • Silicone hydrogel composition and lens produced by the same

    JP2017203155A

  • Hydroxyphenyl naphthotriazoles as polymerizable blockers of high energy light

    US20190002415A1

  • Monomer composition for contact lens, polymer thereof, contact lens, and production method thereof

    WO2020054711A1